Chemical And Organoleptic Characteristics Of Snack Bars Based On Yellow Sweet Potato Flour (Ipomoea batatas L) And Mung Bean Flour (Vigna radiata) - Dwi Putriana Solin; Maya M. Ludong; Jolanda Ch. E. Lamaega (Sam Ratulangi University, 2022)
ABSTRACT The purpose of the study was to analyze the characteristics of chemistry, test the favorability level of panelists, and determine the best treatment of snack bars based on yellow sweet potato flour and green bean flour. Snack bar is a snack in the form of bars made from cereals or beans and snack bars are usually used for breakfast or as snacks. This research method uses the Complete Randomized Design (RAL) research method with 4 treatments of 3 repetitions, namely with treatment A (80% yellow sweet potato flour and 20% mung bean flour), B (70% yellow sweet potato flour and 30% mung bean flour), C (60% yellow sweet potato flour and 40% mung bean flour), D (50% yellow sweet potato flour and 50% mung bean flour). The parameters tested in this study were chemical analysis (water content, protein content, and carbohydrate content) and test the organoleptic (taste, aroma, color, and texture). Based on the panelists' favorability level test for the most preferred snack bar as a whole, it was the mixing of 70% yellow sweet potato flour: 30% mung bean flour, in terms of color 3.52 (likes), aroma 3.72 (likes), taste 3.48 (neutral) and 3.76 textures (likes) with chemical characteristics namely water content 11.96%, protein content 7.58% and carbohydrate content 48.67%. Keywords: Snack bar, Yellow Sweet Potato Flour, Mung Bean Flour. ABSTRAK Tujuan penelitian untuk menganalisis karakteristik kimia dan uji tingkat kesukaan panelis serta menentukan perlakuan terbaik snack bar berbasis tepung ubi jalar kuning dan tepung kacang hijau. Snack bar merupakan makanan ringan yang berbentuk batangan berbahan dasar sereal atau kacang-kacangan dan snack bar biasanya digunakan untuk sarapan atau sebagai makanan ringan. Penelitian ini menggunakan metode penelitian Rancangan Acak Lengkap (RAL) dengan 4 perlakuan 3 kali pengulangan yaitu dengan perlakuan A (80% tepung ubi jalar kuning dan 20% tepung kacang hijau), B (70% tepung ubi jalar kuning dan 30% tepung kacang hijau), C (60% tepung ubi jalar kuning dan 40% tepung kacang hijau), D (50% tepung ubi jalar kuning dan 50% tepung kacang hijau). Parameter yang diuji pada penelitian ini adalah analisis kimia (kadar air, kadar protein, dan kadar karbohidrat) dan uji organoleptik (rasa, aroma, warna, dan tekstur). Berdasarkan uji tingkat kesukaan panelis terhadap snack bar yang paling disukai secara keseluruhan adalah pencampuran 70% tepung ubi jalar kuning: 30% tepung kacang hijau, dari segi warna 3,52 (suka), aroma 3,72 (suka), rasa 3,48 (netral) dan 3,76 tekstur (suka) dengan karekteristik kimia yaitu kadar air 11,96%, kadar protein 7,58% dan kadar karbohidrat 48,67%. Kata kunci : Snack bar, Tepung Ubi Jalar Kuning, Tepung Kacang Hijau.